Increasing the Biological Activity of Salinated Soils of Bukhara Region With the Help of Various Fertilizers (Texas Journal of Agriculture and Biological Sciences, 2022)
In the life of all living organisms in nature, green plants, their blue masses and products obtained from them are of great importance in the active exchange of substances and elements, especially carbon from the main elements and its cycle. The organic and inorganic substances in the soil, especially the wide spread, variety, and enzymatic activity of microorganisms, are very important and significant for the growth, development and fruitful production of plants